PENDAMPINGAN PENGEMBANGAN EDUWISATA BERBASIS SUMBER DAYA LOKAL DI DESA KEKAIT, KECAMATAN GUNUNGSARI, KABUPATEN LOMBOK BARAT - Fathurrahman, Fathurrahman; Slamet Mardiyanto Rahayu; Aminy, Muhammad Habibullah (Nusantara Hasana Journal, 2024)
Kekait is one of the villages included in Gunungsari District, West Lombok Regency. Local resources in Kekait Village have the potential to develop educational tourism. Educational tourism is a form of travel that combines tourism activities with educational aspects. Based on community service activities, it can be seen that youth in Kekait Village, among other things: better understand local resources in Kekait Village, better understand about community as a local resource, and better understand the role of local resources in developing edutourism in Kekait Village.